Peningkatan Keterampilan Menulis Cerpen dengan Latihan Terbimbing Siswa Kelas X.2 SMAN 6 Padang - Suriyani, Siska; Nursaid, Nursaid; Zulfikarni, Zulfikarni (Universitas Negeri Padang, 2013)
The purposes of this article is to explain the process and the improvement Â ability to write a short story using guided exercises at X.2 SMAN 6 Padang student. This type of research finished by using descriptive method trough four stages in each cycle ie planning, action, observation and reflection. The research data in the form of short stories written tests, interviews, observations and field notes sheet student. Based on the results of the study concluded that the precycle average is 46,11% of the students qualified nearly enough, in cycle 1 is sufficiently increasedÂ to 65,29% in cycle 2 andÂ the average value of student learning to write short stories increased to 89,61% with exelent qualifications.